Aspek Keadilan dalam Pengupahan pada UMKM di Indonesia - Lidia Febrianti; Puti Mayang Seruni; Nadia Aulia (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
MSMEs contribute 60.5% of Indonesia's total GDP, with a national workforce absorption rate of 96.9% in 2022. This makes MSMEs a critical engine for national economic progress. The government's enthusiasm for supporting MSMEs is demonstrated, among other things, through special wage regulations for MSMEs, which are lower than the minimum wage, as outlined in Government Regulation Number 36 of 2021 concerning Wages. The policy is beneficial for MSMEs with limited capital because they are exempt from the usual minimum wage obligations. However, this wage is a tragedy for MSME workers, as it is low and insufficient to meet a decent standard of living. This research examines in depth whether the wage policy for MSME workers has met the aspect of justice in industrial relations, considering that Article 27, paragraph 2 of the 1945 Constitution firmly states that